ANTESEDEN NIAT UNTUK KELUAR DI INDUSTRI PERHOTELAN: TINJAUAN LITERATUR SISTEMATIS - Putra, I Ketut Johny Pramanda; Supartha, I Wayan Gede; Rahyuda, Agoes Ganesha; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2025)
Previous research states that in developed and developing countries turnover cases still cost companies significantly, coupled with the phenomenon that in 2024 many professionals intend to resign from their jobs. This research aims to systematically summarize the antecedents of turnover intention in the hospitality industry. The literature review process uses a narrative approach, namely the Systematic Literature Review (SLR) technique and meta-analysis by collecting 345 articles from Harzing's Publish or Perish search engine sourced from the Scopus and Google Scholar databases and finding 22 relevant Q1 articles that discuss turnover intention in the hospitality industry. The results of this study conducted a mapping and showed that individual internal factors such as emotional exhaustion, feelings of psychological contract violation, feelings of job insecurity are antecedents that tend to have more influence on intention to leave the organization than external factors still tend to be very rarely used as antecedents in research related to turnover intention, especially in the hospitality industry, although external factors also have a significant effect on turnover intention. This shows that external factors are still very open and interesting to be studied for further research. And this research provides a summary that can provide practical benefits for hospitality industry management in identifying the causes of high employee turnover intention.